2021
DOI: 10.1155/2021/5884174
|View full text |Cite|
|
Sign up to set email alerts
|

Cloud Computing into Respiratory Rehabilitation Training-Assisted Treatment of Patients with Pneumonia

Abstract: In order to study the therapeutic effect of respiratory rehabilitation training on patients with pneumonia, this paper proposes an integrated adjuvant therapy program based on the cloud computing model. A total of 60 pneumonia patients admitted to Zhujiang Hospital of Southern Medical University from January to July 2020 were selected as the research objects and Southern Medical University pneumonia patients as the research object, to be evenly divided into two groups, each group of 30 people. The control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%